Potential PET tracers for imaging of tumor-associated macrophages - Bruna Fernandes; Paula Kopschina Feltes; Carolina Luft; Luiza Reali Nazario; Cristina Maria Moriguchi Jeckel; Ines F. Antunes; Philip H. Elsinga; Erik F. J. de Vries (SpringerOpen, 2022)
Abstract The increasing incidence of cancer over the years is one of the most challenging problems in healthcare. As cancer progresses, the recruitment of several immune cells is triggered. Infiltration of tumor-associated macrophages (TAMs) is correlated with poor patient prognosis. Since TAMs constitute a big portion of the tumor mass, targeting these cells seems to be an attractive approach for cancer immunotherapy. Additionally, TAM assessment using non-invasive imaging techniques, such as positron emission tomography (PET), might provide a better understanding of the role of TAMs in cancer, and a means for tumor profile characterization, patient selection for individualized immunotherapy and treatment monitoring. Imaging of TAMs using PET tracers is still in its infancy. TAMs have several characteristics that could be exploited as potential targets for imaging. Various PET tracers for these TAM biomarkers have been developed, although often in the context of (neuro)inflammatory diseases rather than cancer. Since macrophages in inflammatory diseases express similar biomarkers as TAMs, these PET tracers could potentially also be applied for the assessment of TAMs in the tumor microenvironment. Therefore, the present review provides an overview of the TAM biomarkers, for which potential PET tracers are available and discusses the status of these tracers.